Paryski dandys. Eugeniusz Sue we "Wspomnieniach" Ernesta Legouvégo = The Parisian dandy. Eugene Sue in "the memories" of Ernest Legouvé - Krysowski, Olaf (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article presents a portrait of E. Sue as a dandy in the light of memories of Sue`sfriend - E. Legouve. A context of the letters of Ch. Baudelaire and the Goncourt brothers is alsovery important. Sue`s dandyism is seen in his work as a director and the manner in which playeda comedy of his own life. There is a certain paradox: Sue was a real dandy whose dandyism is seenas a vocation.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); wspomnienia